(untitled) (Journal of Medical & Health Sciences Review, 2025)
A 75-day feeding trial was conducted in a 2×2 factorial design to evaluate the effects of varying dietary lipid/protein ratios on the growth performance, hepatic enzymes, and metabolic responses of Labeo rohita (initial weight: 2.87 ± 0.01 g). Four pelleted diets containing protein levels of 250 and 300 g kg⁻¹ and lipid levels of 75 and 95 g kg⁻¹ were formulated and fed to fish (n = 10) randomly distributed into four triplicate groups (T1–T4). Fish receiving the 95/300 g kg⁻¹ lipid/protein diet (T4) attained significantly higher (p<0.05) average wet weight, fork length, total length, nitrogen conversion ratio, and protein efficiency ratio. However, the same diet also induced significantly elevated (p<0.05) hepatic alkaline phosphatase, alanine transaminase, and aspartate transaminase activities, indicating enhanced metabolic load on the liver. Bilirubin concentrations remained consistently low across all treatments. In contrast, fish fed the 75/250 g kg⁻¹ lipid/protein diet (T1) showed significantly higher (p<0.05) serum globulin levels, suggesting an immunological benefit. Nitrogen incorporation efficiency, hepatic albumin, total protein, and gamma-glutamyl transferase did not vary significantly (p>0.05) among treatments. Overall, these findings suggest that a 95/300 g kg⁻¹ lipid/protein diet improves growth performance of Labeo rohita but may impose hepatic stress, while lower lipid/protein levels support certain immune parameters.